Corporate social responsibilities and corporate performance through work ethics and affective commitment in ADNOC - Alantali, Abdulla Mohamed (2024)
The importance of Corporate Social Responsibility (CSR) to Abu Dhabi National Oil Company (ADNOC) lies in its potential to enhance corporate performance, stakeholder relationships, and company reputation. However, practical gaps exist in understanding the specific issues related to the implementation and effectiveness of CSR initiatives within the UAE's oil and gas sector. Additionally, theoretical gaps persist in the integration of employee affective commitment and work ethics into the CSR performance nexus. This study investigates the influence of Corporate Social Responsibility (CSR) on corporate performance within Abu Dhabi National Oil Company (ADNOC), focusing on the mediating roles of affective commitment and the moderating roles of work ethics. While CSR practices are widely recognized for their impact on stakeholder relationships and company reputation, the specific dynamics of how CSR interacts with employee affective commitment and work ethics within the context of the UAE oil and gas sector remain underexplored. This research aims to fill these practical and theoretical gaps by examining the direct and indirect effects of CSR on corporate performance at ADNOC. The study was motivated by the practical challenges of implementing CSR in a leading oil and gas company in the UAE, where the effectiveness of these initiatives in enhancing corporate performance has not been sufficiently documented. Theoretically, the research addresses gaps by integrating affective commitment and work ethics into the CSR performance nexus, areas that previous studies have often overlooked. This approach allows for a deeper understanding of the internal mechanisms through which CSR activities influence overall corporate outcomes. Employing a quantitative research design, this study gathered data from 381 employees across various departments at ADNOC using a structured questionnaire. The responses were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) to test the proposed theoretical model. The findings reveal that CSR activities significantly enhance corporate performance, with affective commitment mediating and work ethics moderating these effects in specific domains such as economic, environmental, and philanthropic responsibilities. The results underscore the importance of strategically aligned CSR activities that not only focus on external compliance and achievements but also foster internal commitment and ethical standards among employees. Theoretically, this study contributes to the literature by highlighting the critical roles of affective commitment and work ethics as pivotal elements that enhance the effectiveness of CSR initiatives in improving corporate performance. Practically, it provides insights for policymakers and management at ADNOC and similar organizations to refine their CSR strategies, ensuring they effectively contribute to both social goals and corporate success. This research bridges the identified gaps by demonstrating how integrated CSR approaches can lead to enhanced corporate performance, providing a model for other firms in the industry and broader UAE market to replicate for improved sustainability and stakeholder engagement outcomes.